Sila-bac and molasses additives for high moisture sorghum grain - Heidker, J.I.; Ilg, H.; Behnke, Keith C.; Bolsen, K. (Kansas State University. Agricultural Experiment Station, 2011)
Sila-bac, molasses, or both combined were evaluated as additives for ensiled high moisture sorghum grain. Control grain had the greatest increase in temperature during ensiling. Grain treated with Sila-bac had the highest lactobacilli count but control grain had the fastest drop in pH. Sila-bac grain was the most stable in air and remained stable for 30 days. Control grain was stable for 21 days; grain treated with molasses or molasses plus Sila-bac was stable until day 5. Group-fed steers receiving Sila-bac grain gained faster and were more efficient than steers fed control or molasses-treated grain. Individually fed steers gained fastest when receiving molasses treated grain. Those receiving Sila-bac grain were the most efficient.
Keywords: Beef; Sila-bac; Molasses; Sorghum grain